Silent hunter (Mindscape, 1996)
A role-playing World War II submarine simulator adventure game. Allows the player to choose from a variety of American submarines, prowl the shipping lanes, and steel into enemy harbors. Includes authenic WWII film footage, cinematics, and narration that provide a historically accurate feel for submarine combat. Play historical missions, hypothetical encounters or a career based campaign game.